Proteomics and liquid biopsy characterization of human EMT-related metastasis in colorectal cancer - Huang, Mao-Sen; Fu, Li-Hua; Yan, Hao-Chao; Cheng, Lin-Yao; Ru, Hai-Ming; Mo, Si; Wei, Chun-Yin; Li, Dai-Mou; Mo, Xian-Wei; Tang, Wei-Zhong; Yan, Lin-Hai (Frontiers in Oncology, 2022)
Tumor cells undergo epithelial-mesenchymal transition (EMT), however, there is a room of disagreement in role of EMT heterogeneity to colorectal cancer metastasis (mCRC) evolution. To uncover new EMT-related metastasis proteins and pathways, we addressed the EMT status in colorectal cancer liver metastasis patient-derived CTCs to identify proteins that promote their distant metastasis. And then, we performed a comparative proteomic analysis in matched pairs of primary tumor tissues, adjacent mucosa tissues and liver metastatic tissues. By integrative analysis we show that, unstable Epithelial/Mesenchymal (E/M)-type CTCs had the strongest liver metastases formation ability and the proportion of E/M-type CTCs correlated with distant metastases. Using an optimized proteomic workflow including data independent acquisition (DIA) and parallel reaction monitoring (PRM), we identified novel EMT-related protein cluster (GNG2, COL6A1, COL6A2, DCN, COL6A3, LAMB2, TNXB, CAVIN1) and well-described (ERBB2) core protein level changes in EMT-related metastasis progression, and the proteomic data indicate ERBB2, COL6A1 and CAVIN1 are promising EMT-related metastatic biomarker candidates. This study contributes to our understanding of the role that EMT plays in CRC metastasis and identifies heterogeneous EMT phenotypes as a key piece for tumor progression and prognosis. We further propose that therapies targeting this aggressive subset (E/M-type) of CTCs and related protein may be worthy of exploration as potential suppressors of metastatic evolution.